2015
DOI: 10.1038/srep12732
|View full text |Cite
|
Sign up to set email alerts
|

Methanogenesis from wastewater stimulated by addition of elemental manganese

Abstract: This study presents a novel procedure for accelerating methanogenesis from wastewater by adding elemental manganese into the anaerobic digestion system. The results indicated that elemental manganese effectively enhanced both the methane yield and the production rate. Compared to the control test without elemental manganese, the total methane yield and production rate with 4 g/L manganese addition increased 3.4-fold (from 0.89 ± 0.03 to 2.99 ± 0.37 M/gVSS within 120 h) and 4.4-fold (from 6.2 ± 0.1 to 27.2 ± 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…In the main‐stem, porewater characteristics were generally less important drivers of PMP and PMO spatial variability than sediment indices. A positive relationship between Mn and methane production was also found by Qiao et al () in anaerobic batch experiments with wastewater. Mn may serve as an alternative electron donor for the process of methanogenesis from CO 2 .…”
Section: Discussionsupporting
confidence: 78%
“…In the main‐stem, porewater characteristics were generally less important drivers of PMP and PMO spatial variability than sediment indices. A positive relationship between Mn and methane production was also found by Qiao et al () in anaerobic batch experiments with wastewater. Mn may serve as an alternative electron donor for the process of methanogenesis from CO 2 .…”
Section: Discussionsupporting
confidence: 78%
“…Increased Zn levels have also been shown to stimulate CH4 production in tropical alluvial soils under rice production (Mishra et al 1999). Mn has been shown to stimulate methanogenesis in an anaerobic digester system by acting as an electron donor (Qiao et al 2015), and this has also been shown for Zn (Belay & Daniels 1990). We respectively.…”
Section: This Included Methanogens In the Methanobacteria Methanocelmentioning
confidence: 92%
“…The function of Mn in AD has been described in the literature as a stabilizer for methyltransferase of methanogens [27] and as an electron donor for methane formation from CO 2 [28]. Wu et al (2015) reported that the addition of Mn improved the methanogenic production rate in de-oiled grease trap waste digestion.…”
Section: Metal Effect On Black Water Anaerobic Digestionmentioning
confidence: 99%